Toxoplasma gondii : the model apicomplexan : perspectives and methods - Weiss, Louis M.; Kim, Kami (Elsevier/Academic Press, 2007)
Toxoplasmosis is caused by a one-celled protozoan parasite known as Toxoplasma gondii. In the United States, it is estimated that approximately 30% of cats, the primary carriers, have been infected by T. gondii. Most humans contract toxoplasmosis by eating cyst-contaminated raw or undercooked meat, vegetables, or milk products or when they come into contact with the T. gondii eggs from cat feaces while cleaning a cat's litterbox, gardening, or playing in a sandbox. Approx 1 in 4 (more than 60 million) people in the USA are infected with the parasite, and in the UK between 0.5 and 1% of indivi.